Reference values of the usual biochemical profile in clinically normal cats - FYTIANOU (Α. ΦΥΤΙΑΝΟΥ) A.; SARIDOMICHELAKIS (Μ. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M.; KOUTINAS (Α. Φ. ΚΟΥΤΙΝΑΣ) A. F.; ROUBIES (Ν. ΡΟΥΜΠΙΕΣ) N.; POLIZOPOULOU (Ζ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z. (Journal of the Hellenic Veterinary Medical Society, 2018)
The purpose of this study was the establishment of "reference values" for the commonly used blood serum constituents in the everyday practice. A total number of 23 parameters including total proteins, albumin, globulin, albumin/globulin ratio, urea nitrogen (BUN), creatinine, glucose, cholosterol, triglycerides, total and indirect bilirubin, alkaline phosphatase (AP), gamma - glutamylotransferase (γ-GT), alanine aminotransferase (ALT), aspartate aminotransferase (AST), lipase, amylase, creatinine kinase (CK), lactate dehydrogenase (LDH), calcium (Ca), phosphorus (P), potassium (K) and sodium (Na) in the serum samples obtained from 1ΘΘ clinically normal cats equally distributed into two age groups (group A <12 months, group Β >12 months). For the total number of sampled cats and for each age group the mean, the standard deviation, the actual range and the 95% confidence interval were calculated separately. Statistical analysis revealed significant differences between young and adult cats (group A - group B) for as many as 13 parameters. As it was expected our results are both in agreement and disagreement with those reported in the relevant veterinary literature.